Electronic Data Interchange (EDI): An Interorganizational System Applied in the Auto Parts Industry Supply Chain - Marcelo T Okano; Marcelo Eloy Fernandes (International Journal of Supply Chain Management, 2019)
One of the main advantages offered by Information and Communication Technologies (ICTs) is the exchange of data between organizations, from simple e-mail to the most sophisticated information systems such as Efficient Consumer Response (ECR), Supply Chain Management (SCM) (CPFL), Business-to-business Commerce (B2B) and Electronic Data Interchange (EDI). Complexity increases when we extrapolate the boundaries of companies and integrate the information of several organizations in a shared way, as each company has its own culture. The research work proposed here aims to carry out an exploratory study, which seeks to analyze the implementation of an interorganizational system like EDI in the automobile industry, based on the information and opinions of the managers of small and medium enterprises of the auto parts sector. In order to achieve the objective of this work, a survey was carried out with suppliers of auto parts for the Automobile Industry assemblers, using the EDI. In general, the research indicated that the use of EDI (or interorganizational systems) by auto parts companies is still at a very early stage. When comparing the aspects presented in the theoretical models selected in the literature with the reality of these companies, it is seen that those concepts are, for the most part, far from becoming reality. At the same time, it can be said that the characteristics and benefits obtained from the use of EDI systems are very small, compared with the models presented.